Storage time effect on the quality of fermented milk beverage with coffee and probiotic activity (Research, Society and Development, 2020)
This work was carried out with the objective of optimizing a formulation and verifying the effect of the storage time on the quality characteristics of the fermented milk beverage with coffee and probiotic microorganisms. A complete factorial 23 was used, with two levels (± 1) and three central points (0), totaling 11 formulations. After optimizing of the formulation, analyzes of acidity, viability of the probiotic culture (Lactobacillus acidophilus and Bifidobacterium animalis), acceptance and microbiological in different storage times at 4ºC (0, 7, 14, 21 and 28 days) were performed. The results revealed that the whey concentration did not interfere with the acceptance of the product. Samples 2, 3 and 4 showed an acceptability index above 70%, with sample 4 being chosen to evaluate its behavior during storage. The storage time did not significantly influence (p> 0.05) on acidity and sensory acceptance. The beverages met the microbiological standards recommended by the legislation. The product maintained the probiotic activity for L. acidophilus until the end of the storage, demonstrating that the milk beverage constitutes an important vehicle for inoculation of probiotic bacteria.